KAJIAN YURIDIS PENGEMBALIAN KERUGIAN KEUANGAN NEGARA SEBAGAI ALASAN MERINGANKAN PENJATUHAN PIDANA (Studi Kasus Putusan di Tindak Pidana Korupsi) - Arista Candra Irawati (Fakultas Hukum Universitas Wahid Hasyim, 2019)
Law No. 31 of 1999 concerning Eradication of Corruption Crimes as amended by RI Law No. 20 of 2001 concerning Amendment to Law No. 31 of 1999 in its application can not be separated from the offense / elements of acts against the law. One of the elements in Corruption Crimes is the existence of actions which are detrimental to the State. From one of these elements, as a form of existence due to criminal acts of corruption is detrimental to the State. Furthermore, in the process of returning the State's finances, the Prosecutor's Office has an obligation to return the State through replacement money. In accordance with Article 4 of the Corruption Criminal Act, it is stated,